Lean On Me: The Support Experiences of Black Graduate Students - Juanita Johnson-Bailey; Thomas Valentine; Ronald M. Cervero; Tuere Bowles (Adult Education Research Conference, 2007)
The social support experiences of Black graduate students who graduated from a major Southern Research University from 1962 to 2003 were examined in a comprehensive survey that explored three areas: relationships with faculty, students, and the institution. The study revealed that the Black graduate students believed that White graduate students experienced a different campus and a more positive environment.